2009
DOI: 10.1007/s10529-009-0147-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and expression of a novel holotype crystal protein gene, cry56Aa1, from Bacillus thuringiensis strain Ywc2-8

Abstract: Bacillus thuringiensis isolate Ywc2-8, from soil in Sichuan Basin in western China, contains a spherical crystal harbouring two insecticidal crystal proteins with masses of 70 kDa and 130 kDa. A novel cry-type gene, encoding a 664 amino acid protein with 34% homology to cry29Aa1, was found and cloned from this strain. This gene belongs to a novel holotype cry and is designated as cry56Aa1. It was expressed in E. coli. Insecticidal activity assays showed that recombinant Cry56Aa1 was toxic to both Dipteran (Aed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The identification of vip1Ac1 gene from B. cereus strain HL12 validated that the developed PCR–RFLP was an effective, simple, and reliable method for identifying novel vip1 ‐type genes. According to known partial sequences of vip1 ‐like genes, the full‐length sequence of vip1Ac1 gene was successfully amplified from B. cereus by SON‐PCR method, confirming that SON‐PCR is a reliable and simple method for amplification of unknown gene fragments as previously reported (Antal et al ., ; Zhu et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of vip1Ac1 gene from B. cereus strain HL12 validated that the developed PCR–RFLP was an effective, simple, and reliable method for identifying novel vip1 ‐type genes. According to known partial sequences of vip1 ‐like genes, the full‐length sequence of vip1Ac1 gene was successfully amplified from B. cereus by SON‐PCR method, confirming that SON‐PCR is a reliable and simple method for amplification of unknown gene fragments as previously reported (Antal et al ., ; Zhu et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…With sequences similar to known gene sequences that encode effective insecticidal peptides, PCR–RFLP has been recently applied to identify novel genes (Kuo & Chak, ). Many cry ‐type genes have been identified using PCR–RFLP (Kuo & Chak, ; Song et al ., ; Zhu et al ., , ). However, only a few PCR–RFLP identification systems have been developed for vip genes (Beard et al ., ; Hernández‐Rodríguez et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Saitoh et al [22], Wasano et al [23] and Jung et al [24] reported spherical crystals to be characteristic of Lepidoptera specific Cry9 toxin, mosquitocidal Cry4A and Cry10A toxins and cry31Aa specific to human cancer cells respectively. Recently, Zhu et al [25] reported a novel group of cry56Aa genes from a Bt strain producing spherical crystal inclusions and having broad spectrum of activity. Thus spherical type of crystal inclusion represents comparatively more diverse Cry proteins than the other types.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of Cyt3Aa1 was tested against larvae of A. aegypti (Diptera) as previously described [13]. The hemolytic activity of the Cyt3Aa1 protein was determined using human red blood cells as described by Ragni et al and Juárez-Pérez et al [14] [15].…”
Section: Insecticidal and Hemolytic Activity Assays Of Cyt3aa1mentioning
confidence: 99%